Integration of Character Education in Citizenship Education Learning to Develop the Character of Elementary School Students - Anggraini, Sekar (International Journal of Students Education, 2024)
Education is citizenship, one of the themes that is a leading sector in developing student character. Character education is also an important aspect in the development of students in elementary schools. One of the subjects that has great potential to integrate character education is citizenship education. This approach combines an understanding of the rights and obligations of citizens with the formation of positive and ethical character. This study aims to integrate character education to develop attitudes and characters in elementary school students using a qualitative approach. Then for the method used, namely the literature study method. Where the author collects data from references to articles and journals available on trusted websites. In reality, citizenship education lessons have not been successful enough to carry out this role properly because the processes that occur in educational learning are only activated in achievement, affective management or attitudes are ignored. To overcome this, it is necessary to review modifications in educational learning, one of which is by integrating the concept of character into its development so that it is better able to develop and shape the character of elementary school students.